Clumping of lymphoma cells in peripheral blood induced by EDTA. - Juneja, S. (1992)
A peripheral blood smear from a patient with probable splenic lymphoma with villous lymphocytes (SLVL) showed clumping of lymphoma cells. The clumping was not seen in films made from unanticoagulated blood, and has not been previously described in lymphomas. The patient also had metastatic prostatic adenocarcinoma for 30 months before lymphoma was diagnosed and the clumped cells posed diagnostic problems.